Kontribusi UMKM (Usaha Mikro, Kecil, dan Menengah) Terhadap Pembangunan Ekonomi Nasional - Filza Salsabila Surbakti, Putri; Siregar, Nurhasanah (Philosophiamundi, 2023)
The research aims to determine the contribution of (Micro, Small and Medium Enterprises) to National Economic Development. In this research the author used a library research method, namely collecting and reviewing existing literature from various sources. Journals were searched using Google Scholar. Journal searches were carried out using the keywords MSMEs, national economic development. This research shows that Micro, Small and Medium Enterprises have a significant contribution to national economic development. This research shows that UMKM have great development potential to contribute more to the national economy. The number of MSMEs in Indonesia continues to increase every year and has a large contribution to the country's gross domestic product (GDP). Several previous studies also show that Micro, Small and Medium Enterprises have an important role in national economic development.